2015
DOI: 10.1038/eye.2015.35
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the retinal nerve fibre layer and ganglion cell complex thickness in pituitary macroadenomas without optic chiasmal compression

Abstract: Purpose The aim of this prospective study was to measure the thickness of the circumpapillary retinal nerve fibre layer (cpRNFL) and the ganglion cell complex (GCC) using spectral domain optical coherence tomography (SD-OCT) in a cohort of consecutive de novo patients with pituitary macroadenomas without chiasmal compression. Patients and methods Twenty-two consecutive patients with pituitary macroadenoma without chiasmal compression (16 men, 6 women, aged 45.2 ± 14.6 years, 43 eyes) entered the study between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 26 publications
3
29
0
5
Order By: Relevance
“…Our finding was not in agreement with the opinion that only chiasmal compression would cause visual pathway impairment. Our results were compatible with a prospective study carried out by Cennamo et al 17 . They found that up to 58% of patients suffering PA without chiasmal compression had GCC and cpRNFL loss, although their visual field and visual acuity was normal.…”
Section: Discussionsupporting
confidence: 94%
“…Our finding was not in agreement with the opinion that only chiasmal compression would cause visual pathway impairment. Our results were compatible with a prospective study carried out by Cennamo et al 17 . They found that up to 58% of patients suffering PA without chiasmal compression had GCC and cpRNFL loss, although their visual field and visual acuity was normal.…”
Section: Discussionsupporting
confidence: 94%
“…Útlak OC má vliv na vedení vzruchů zejména ve zkřížených vláknech zrakové dráhy a nejčastěji je diagnostikován přítomností defektu v temporální části zorného pole (ZP) [21,31,32]. K objektivizaci zrakových obtíží se využívá zejména vyšetření ZP, ačkoliv nemusí vždy jednoznačně odhalit patologii [4]. V posledních dekádách se častěji využívá optická koherenční tomografie (OCT) v diagnostice kompresivních lézí částí zrakové dráhy tvořené vlákny gangliových buněk.…”
Section: úVodunclassified
“…Na druhé straně argumentační osy je například publikace Cennamo a spol. [4]. Při jasné absenci tlaku adenomů hypofýz naměřili patologické hodnoty RNFL i GCC svědčící pro kompresi OC u jedinců, kteří neměli žádná jiné onemocnění zrakového ústrojí.…”
Section: Diskuseunclassified
“…[ 7 ] The macular ganglion cell complex consists of three retinal layers, including the nerve fiber layer (NFL), the ganglion cell layer (GCL), and the inner plexiform layer (IPL) and can be measured by SD-OCT; thus, many trials have evaluated the macular ganglion cell complex using SD-OCT in patients with many optic nerve disorders. [ 8 12 ]…”
Section: Introductionmentioning
confidence: 99%